Severe skin and subcutaneous pythiosis in China: Metagenomic identification and characterization of Pythium insidiosum - Zhang, Haiyan; Zhou, Fengli; Huang, Jiabao; Liu, Xiaoyun; Xu, Hui; Liang, Jiayin; Wang, Jun; Chen, Jing; Liu, Lingling; Li, Yiting; Hu, Xuan; Chen, Xuanrong; et al. (Frontiers in Microbiology, 2022)
Pythium insidiosum is a rare fungus-like pathogen that is known to cause pythiosis in mammals with high morbidity and mortality. Identification of the pathogen is essential for timely treatment and rational use of antibiotics. However, Pythium insidiosum is difficult to detect via conventional microbiological tests. The current gold standard is polymerase chain reaction, which is lacking in most hospitals since human pythiosis is rare in China. In this study, we used metagenomic Next-Generation Sequencing and identified Pythium insidiosum in a 56-year-old Chinese male who was hospitalized due to severe edema in the right lower limb with scattered darkening indurations. The patient had a history of cirrhosis and occupational exposure to swamp water. Serological level of immune biomarkers indicated immunodeficiency, and Proteinase 3-Anti-Neutrophil Cytoplasmic Antibody was positive. Surgical incision of the lesions revealed radiating and reticular cutaneous ulcers. Microbial infections were suspected but conventional tests failed to discover the etiology. Empirical use of penicillin, vancomycin, and ceftriaxone had no effect. As a result, the peripheral blood and tissue biopsies were sent for metagenomic Next-Generation Sequencing, which reported Pythium insidiosum. This finding was corroborated by pathological staining, whole-genome sequencing, and internal transcribed spacer sequencing. Notably, antifungal treatment was ineffective, but the patient responded well to oral trimethoprim–sulfamethoxazole, which may be due to the folp gene found in Pythium insidiosum genome. Our study prompts future studies to determine the optimal treatment of skin pythiosis.